Phacomatosis pigmentokeratotica: a case with a broad spectrum of systemic involvement. - Fernandes César, A.J.; Cruz, M.J.; Vieira Mota, A.; Azevedo, F. (European Journal of Pediatric Dermatology, 2015)
Phacomatosis pigmentokeratotica (PPK) is a type of epidermal nevus syndrome characterized by the co-occurrence of sebaceous nevus (SN) and papular speckled lentiginous nevus (SLN). The Authors describe the case of a full-term newborn boy with this rare condition and extracutaneous abnormalities: aortic coarctation, "absences", an arachnoid cist, left criptorquidism and hypoplasia of the left kidney. The SN affected the scalp, forehead, nose, lower lip, neck and trunk, following Blaschko’s lines. The papular SLN extended from the lower torso to the right leg. This case presents a combination of neurological, cardiac and genitourinary abnormalities uncommon in most previous case reports. This multisystem character of PPK underlines the importance of a multidisciplinary team approach to ensure adequate diagnosis, treatment and follow-up.